1984
DOI: 10.1177/027614678400400202
|View full text |Cite
|
Sign up to set email alerts
|

Macromarketing: A Social Systems Perspective

Abstract: The marketing system is a differentiated subsystem of the society, performing functions necessary if society is to adapt to its material environment. In the performance of these functions, the marketing system has an impact on other social systems, the cultural system, and the material environment. This dual relationship is derived from a modified social systems paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 8 publications
1
49
0
Order By: Relevance
“…In this new approach, the focus is on the characteristics of the emerging country. In this way, it is possible to imagine a development path that is tailor-made, based on the involvement of local actors and truly sustainable [16][17][18][19][20]. This literature supported the design of the method used for this paper.…”
Section: Overview Of the Literature On Development (Objective 1)mentioning
confidence: 69%
“…In this new approach, the focus is on the characteristics of the emerging country. In this way, it is possible to imagine a development path that is tailor-made, based on the involvement of local actors and truly sustainable [16][17][18][19][20]. This literature supported the design of the method used for this paper.…”
Section: Overview Of the Literature On Development (Objective 1)mentioning
confidence: 69%
“…Based on the respondents' narratives, we identified an initial characteristic of the clothing disposal system by gifting: it is non-centric. The presence of a large number of actors, with no central coordination, endows this system with its non-centric character (Dixon, 1984). A second feature arising from the narratives demonstrated that the system is based on social exchange.…”
Section: The Clothing Disposal System By Gifting and Its Featuresmentioning
confidence: 99%
“…Marketing activities can also be assimilated into a system (Dixon, 1984;Meade & Nason, 1991). In the current study, the clothing marketing system is relevant, involving the manufacturers and retailers of new clothing, as well as the consumers and products.…”
Section: The Clothing Disposal System By Gifting and The Clothing Marmentioning
confidence: 99%
“…The holistic impact of marketing systems was also reflected in Dowling's (1983) definition which specified marketing systems as complex social dynamics which revolve around managing decisions on production, consumption and distribution. Dixon (1984) identified marketing systems as a differentiated subsystem of society. However, Arndt (1986) viewed the marketing system as a network of relationships which is assumed to be constant for a long period of time.…”
Section: Literature Reviewmentioning
confidence: 99%